Simulasi Pengadaan Barang Menggunakan Metode Monte Carlo - Manurung, Kiki Hariani; Santony, Julius (Jurnal Sistim Informasi dan Teknologi, 2019)
Inventory is a very important aspect for the development of a company. Inventory management is needed to determine the inventory of goods needed within a certain period so that market demand can be fulfilled. The data used in this study are inventory data 2016. Data processing in this study uses the Monte Carlo algorithm to predict procurement data. In accelerating data processing, this research applies a Web-based program with the PHP (Hypertext Processor) programming language. The results of testing this method are to obtain predictions of the supply of goods in a certain period of time with the right level of accuracy. From the test results obtained the level of accuracy in predicting inventory stock by 93% so that it can help companies in making decisions in the future.